The Novel Chinese Medicine JY5 Formula Alleviates Hepatic Fibrosis by Inhibiting the Notch Signaling Pathway - Fu, Yadong; Xiao, Zhun; Tian, Xiaoting; Liu, Wei; Xu, Zhou; Yang, Tao; Hu, Yonghong; Zhou, Xiaoxi; Fang, Jing; Gao, Siqi; Zhang, Dingqi; Mu, Yongping; et al. (Frontiers in Pharmacology, 2021)
Advanced liver fibrosis can lead to cirrhosis, resulting in an accelerated risk of hepatocellular carcinoma and liver failure. Fuzheng Huayu formula (FZHY) is a traditional Chinese medicine formula treated liver fibrosis in China approved by a Chinese State Food and Drug Administration (NO: Z20050546), composed of Salvia miltiorrhiza Bge., Prunus davidiana (Carr.) Franch., cultured Cordyceps sinensis (BerK.) Sacc. Mycelia, Schisandra chinensis (Turcz.) Baill., Pinus massoniana Lamb., and Gynostemma pentaphyllum (Thunb.) Makino. However, the main active substances and mechanism of action are unclear.This study aimed to identify a novel anti-fibrotic compound, which consists of the main active ingredients of FZHY formula, and investigate its mechanism of pharmacological action.The main active ingredients of FZHY were investigated by quantitative analysis of FZHY extracts and FZHY-treated plasma and liver in rats. The anti-fibrotic composition of the main active ingredients was studied through uniform design and validation experiments in vivo, and its mechanism was evaluated in carbon tetrachloride (CCl4)- and bile duct ligation (BDL)-induced liver fibrosis models in rats and mice, and transforming growth factor beta 1-induced LX-2 cell activation model in vitro.A novel Chinese medicine, namely JY5 formula, consisting of salvianolic acid B, schisantherin A, and amygdalin, the main active components of FZHY, significantly alleviated hepatic hydroxyproline content and collagen deposition in CCl4- and BDL-induced fibrotic liver in rats and mice. In addition, JY5 inhibited the activation of hepatic stellate cells (HSCs) by inactivating Notch signaling in vitro and in vivo. In this study, we found a novel JY5 formula, which exerted anti-hepatic fibrotic effects by inhibiting the Notch signaling pathway, consequently suppressing HSC activation. These results provide an adequate scientific basis for clinical research and application of the JY5 formula, which may be a potential novel therapeutic candidate for liver fibrosis.